Robinsonaden som 1800-tallets eksemplariske oppdragelsesfortelling - også for jenter - Rønning, Anne Birgitte (Tidsskrift for kulturforskning, 2010)
By the end of the 18th century the robinsonade became a genre primarily of juvenile fiction. This development was influenced by Jean-Jacques Rousseau who in Emile (1762) had claimed Daniel Defoe’s Robinson Crusoe (1719) to be the only book worth reading for his pupil. This paper presents and discusses the robinsonade as an exemplary pedagogical genre and its attraction, in spite of its basically male paradigm, to both female authors and the discussion of girls’ education. It examines juvenile robinsonades with female castaways and reveals different gendered adaptations to the story of survival as well as to the discourse of education. As female protagonists do not fit seamlessly in to the generic model, the texts expose the ambivalences of the generic model as such, and of the conceptions of exemplarity based on Rousseau. The analysis of exemplarity concentrates on the enactment and framing of the castaway story, as well as on the presentation of the protagonist oscillating between representativeness and uniqueness.